Comparison the Effect of Neuromuscular Exercises With Other Training Modalities on Balance and Motor Function in People With Chronic Ankle Instability: A Systematic Review and Meta-Analysis - Ali Fatahi; Mahboobeh Dehnavi (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective Identifying the factors affecting the reduction of ankle sprain complications, rapid recovery, and prevention of re-injury after an ankle sprain are essential. Therefore, the present meta-analysis investigates which training modalities have a better effect on the balance and motor function of people with chronic ankle instability. Materials & Methods The relevant articles were identified by searching 8 international databases of MEDLINE/PubMed, Embase/Scopus, LILACS, CINAHL, Central (Cochrane Central Register of Controlled Trials), Web of Science, PEDro, and Google Scholar. This work was also done in Persian databases Magiran, Irandoc, Iranmedex, MedLib, and SID, equivalent to English keywords searched from 8 databases. After collecting the search results, first, the title and then the abstracts of the articles were read. If the articles met the inclusion and exclusion criteria, their results would be used in the review study, otherwise discarded. The search period comprised from the beginning to December 2021. In addition, a manual search and full review of article sources was performed. The exclusion criteria were articles whose statistical population was people other than people with chronic ankle instability, published articles other than English and Persian, and articles that examined the effect of exercise programs on factors other than balance and motor function had paid. Hedges' effect size (ratio of the mean difference between the two groups to the mixed weight standard deviation) was used for meta-analysis. Heterogeneity between studies was assessed using the I2 index. If the heterogeneity is above 50%, the random effects model method is used, and if it is below 50%, the fixed-effects model method is used. The bias of published studies was assessed using Egger's test. Comprehensive meta-analysis v.2.0 software was used to analyze the data. Results After reviewing the full text of the found articles, 21 articles using 24 training protocols were selected. The final articles were divided into two categories for analysis: articles comparing neuromuscular exercises with other exercises and articles comparing new and combined balance exercises with other exercises with traditional balance exercises. By a superficial qualitative review of articles with the PEDro tool, the average scores that articles received from this scale were higher than 7, which shows that the articles used for the meta-analysis of this study are of high quality and the results of these studies are reliable. Conclusion The results of studies showed that neuromuscular training has a better effect on static and dynamic balance in people with chronic ankle instability than other training protocols. However, there was no significant difference between the two types of training groups in motor performance. The results of studies also showed that balance-combination exercises, as well as new methods of balance exercises compared to traditional balance exercises, have a more significant effect on static balance and motor function of people with chronic ankle instability. However, no significant difference between the two types of training groups was observed in the dynamic balance. Also, the effect of new combined-balance exercises on dynamic balance was better than traditional balance exercises. It seems that the usefulness of balance-combination exercises and performing balance exercises with new methods is more useful than other training protocols on balance and postural control of people with chronic ankle instability.